Cost-Benefit Analysis of Masculinising Nile Tilapia (Oreochromis Nilotus, Linnaeus 1758) using Camel Testicles-Based Diet - Mohammed, Z.B.; Umar, H. M.; Aliyu, M.; Suleiman, S. B.; Gamawa, A. I. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
Cost-benefit analysis of masculinizing nile tilapia (Oreochromis niloticus, Linnaeus 1758) using camel testicle-based diet was carried out in Maiduguri. The aim was to determined cost and benefit of masculinising and growing nile tilapia using less expensive materials (camel testicles). Fresh camel testes were collected from Maiduguri abattoir and processed into a meal. The camel testicles meal was added to 40% crude protein formulated diet at various proportions of 0, 0.25, 0.50, 0.75 and 1.00%to replace fish meal and fed to 7-day old fries which were kept indoors for forty (40) days. The 40-day old fries were assessed for number of males and females. Thirty (30) fries from each treatment were collected and reared for growth performance for another 90 days. The benefit cost analyses of masculinising the fish were determined for each replacement level. Lower cost of feed production, total input cost and benefit ratio (₦340,2350 and 1.55, respectively) were shown in fries fed 1.00%camel testicle diet while the least benefit ratio was in fries fed0.75% camel testicle diet. Inclusion of camel testicle diet at 1.00% can be used to masculinise nile tilapia with a high benefit.